The Use of Tracker Application to Enchance Physics Teachers in Senior High School in Making Laboratory Video - Yulkifli Yulkifli; Ramli Ramli (Pelita Eksakta, 2018)
During this time, practicum activities in the School have not gone well. In fact, practical activities can support the understanding of the theory or material Physics taught to students. In addition, the lab can also generate student motivation and passion, as well as develop the students' process skills by conducting experiments. Experimental activities are very useful for students if this activity has been planned and designed well by teachers. Currently, technological advances can help improve Physical practice in the School. One of them by using video based laboratory (VBL). VBL is a practical activity in the laboratory in the form of video-based educational software. Technical Guidance for Making Video-Based Laboratory Application Tracker for Physics Teacher in Teachers' Consultation in Subject (MGMP) of High School Physics (SMA) in Padang and Padang Panjang City ", This activity was held for 2 months with the activity stage is preparation, implementation and activity evaluation. Based on the planning, the activities have been successfully done well. Implementation of this activity by the way the teacher is guided using the application Tracker on Physics practicum activities. The output of this activity is the Digital Video Labaratory for teaching material with Tracker application for physics practicum activity, especially Regular Straight Motion (GLB), Straight Changed Motion (GLBB), Momentum and Impulse.